Should we be more cre‐tical? A cautionary tale of recombination - Andrusaite, Anna (Immunology, 2020)
The cre‐loxP system has been revolutionary in the field of immunology. The technology enables genetic deletion in mice with unprecedented precision. It is therefore now widely used to investigate gene functions in animal models of disease, and in fundamental studies of the immune response. This widespread adoption of cre‐loxP technology has allowed a thorough investigation of its strengths and weaknesses. Here we highlight an important paper which not only describes potential problems with the commonly‐used screening procedures used when identifying offspring of the correct genotype, but also describes how this screening can be improved to ensure that the right animals are produced.